ANALISIS PENGARUH FIRM SIZE, GROWTH OPPORTUNITY, FIRM AGE, LEVERAGE, DAN NON-CASH NET WORKING CAPITAL TERHADAP CASH HOLDING (Studi pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019) - Alda Aspasia, Donna Bella; Arfianto, Erman Denny (Diponegoro Journal of Management, 2021)
Every company has their respective preferences in determining the amount of cash to be held in a period of time. Previous studies have discussed the factors that determine cash holdings. However, there are still inconsistencies in the research results so that further research is needed to examine the factors that affect the company's cash holdings. Thus, the aims of this study were to determine the factors that influence cash holdings.Â The sample used in this study is a manufacturing company listed on the IDX (Indonesia Stock Exchange) during the 2016-2019. The samples observed was 112 companies with a total of 444 observations which taken by purposive sampling method. The method of analysis of this study uses linear regression which has previously passed the classical assumption test.The results of this study indicated that Growth Opportunity had a positive and significant effect on Cash Holdings. Firm Size, Leverage, and Non-cash Net Working Capital had negative and significant effect on Cash Holdings. Meanwhile, Firm Age had a negative-but-insignificant effect on Cash Holdings.